IMPLEMENTASI MODEL PEMBELAJARAN DEEP LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MATERI LARANGAN BUGHAT - Annisaul Karimah; Muhammad Nur Hadi; Muhammada Muhammada; Anang Sholikhudin (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
ABSTRACT Fiqh learning, particularly on the topic of the prohibition of bughat (rebellion against legitimate authority), requires not only mastery of religious concepts but also students’ ability to understand their relevance to social life. In practice, student engagement in the learning process is often less than optimal when instruction is predominantly centered on teacher-led content delivery. This situation encouraged the implementation of the Deep Learning approach at MA As-Sholchah as an effort to create more meaningful learning experiences and enhance students’ learning motivation. This study employed a qualitative case study design involving one Fiqh teacher and 30 eleventh-grade students. Data were collected through observations, interviews, and documentation and were analyzed using the interactive model of Miles and Huberman. The trustworthiness of the findings was strengthened through triangulation of data sources and collection techniques. The findings reveal that the integration of the principles of mindful learning, meaningful learning, and joyful learning transformed the classroom atmosphere into a more participatory learning environment. Students were not merely recipients of information; they actively engaged in discussions, case analyses, and reflective activities that fostered a deeper understanding of socio-religious issues. These changes were reflected in increased self-confidence, enthusiasm, and active participation throughout the learning process. By providing contextual and collaborative learning experiences, the Deep Learning approach contributed positively to strengthening students’ learning motivation while helping them develop a more comprehensive understanding of the Fiqh concepts being studied. ABSTRAK Pembelajaran Fiqih, khususnya pada materi larangan bughat, tidak hanya menuntut penguasaan konsep keagamaan, tetapi juga kemampuan siswa untuk memahami relevansinya dalam kehidupan sosial. Kenyataannya, keterlibatan peserta didik dalam proses belajar sering kali belum optimal ketika pembelajaran lebih banyak berfokus pada penyampaian materi oleh guru. Situasi tersebut mendorong penerapan pendekatan Deep Learning di MA As-Sholchah sebagai upaya menghadirkan pengalaman belajar yang lebih bermakna dan mampu menumbuhkan motivasi belajar siswa. Kajian ini dilakukan melalui studi kasus kualitatif dengan melibatkan satu guru Fiqih dan 30 siswa kelas XI. Informasi penelitian diperoleh melalui observasi, wawancara, dan dokumentasi, kemudian ditafsirkan menggunakan analisis interaktif Miles dan Huberman. Keabsahan temuan diperkuat melalui triangulasi berbagai sumber dan teknik pengumpulan data. Temuan menunjukkan bahwa integrasi prinsip mindful learning, meaningful learning, dan joyful learning mengubah suasana pembelajaran menjadi lebih partisipatif. Siswa tidak hanya menerima materi, tetapi juga terlibat dalam diskusi, analisis kasus, dan kegiatan reflektif yang mendorong pemahaman lebih mendalam terhadap persoalan sosial-keagamaan. Perubahan tersebut tampak pada meningkatnya kepercayaan diri, antusiasme, serta keterlibatan aktif siswa selama proses pembelajaran berlangsung. Pengalaman belajar yang kontekstual dan kolaboratif menjadikan pendekatan Deep Learning berkontribusi positif dalam memperkuat motivasi belajar sekaligus membantu siswa membangun pemaknaan yang lebih utuh terhadap materi Fiqih yang dipelajari.